2024
DOI: 10.1111/sms.14584
|View full text |Cite
|
Sign up to set email alerts
|

A “test in‐train out” program versus a “go home and walk” intervention for home‐based exercise therapy in patients with peripheral artery disease: A randomized controlled trial

Fabio Manfredini,
Luca Traina,
Valentina Ficarra
et al.

Abstract: ObjectiveIn this single‐blinded randomized controlled trial, we compared the “Test in‐Train Out” structured home‐based exercise program (TiTo‐SHB) with the traditional “go home and walk” exercise intervention in people with peripheral artery disease (PAD).MethodsPeripheral artery disease patients at Leriche‐Fontaine's stage II were randomized to receive TiTo‐SHB or walking advice (C‐WA). The TiTo‐SHB group performed two daily 8‐min sessions of pain‐free interval walking at progressive low‐to‐moderate speed mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(167 reference statements)
0
2
0
Order By: Relevance
“…The Ex group was also characterized by fewer vascular procedures than the revascularization group, probably due to the systemic effect of the structured exercise. In particular, the TiTo program, administered to the subjects in the present study, was found to be effective at determining hemodynamic peripheral adaptations in the arteries of both the lower and upper limbs [ 40 , 41 , 42 , 43 , 44 ], resulting in a low revascularization rate 3 years after discharge from the program [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Ex group was also characterized by fewer vascular procedures than the revascularization group, probably due to the systemic effect of the structured exercise. In particular, the TiTo program, administered to the subjects in the present study, was found to be effective at determining hemodynamic peripheral adaptations in the arteries of both the lower and upper limbs [ 40 , 41 , 42 , 43 , 44 ], resulting in a low revascularization rate 3 years after discharge from the program [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, considering a minimal clinically important difference for walking speed set at 20%, Straudi et al observed that most of the responders were PwMS that walked slower at the pretreatment assessment. 14 Benefits of low-intensity training at progressively increasing intensity have also been observed in PwMS when empowered by blood flow restriction, 15 muscular and haemodynamic responses in diseases such as peripheral arterial disease, [16][17][18] stroke 19 20 and dialysis patients. [21][22][23] From a neurological point of view, there is limited information regarding the mechanisms of cerebral reorganisation after gait rehabilitation using RAGT.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%